An Ordinance Prohibiting the Unlawful Carrying of Arms, DAILY DEMOCRATIC STATESMAN, May 29, 1880, at 4 (Austin, TX) §§ 1-2 - (:unkn) unknown (My University, 1880)
Prohibited the carry on or about his person, saddle, or saddle bags in the city hall any pistol, dirk, dagger, slung-shot, sword-cane, spear, brass knuckles, Bowie-knife, or other kind of knife manufactured or sold for purposes of offense or defense.
Keywords: SENSITIVE PLACES